Optimizing the Crystal Habit of Glycine by Using an Additive for Impinging Jet Crystallization. Issue 7 (9th June 2017) - Tari, Tímea; Ambrus, Rita; Szakonyi, Gerda; Madarász, Dániel; Frohberg, Patrick; Csóka, Ildikó; Szabó-Révész, Piroska; Ulrich, Joachim; Aigner, Zoltán
Abstract: Additives selectively inhibit or enhance the growth of crystal faces and effectively change the crystal morphology. For the first time, potassium chloride was used as additive during impinging jet crystallization of glycine. The structure of the powder particles was evaluated by X‐ray powder diffraction, differential scanning calorimetry, scanning electron microscopy with energy dispersive X‐ray spectroscopy, headspace gas chromatography, and flame atomic absorption spectrometry. Even a minor amount of KCl had a significant effect on the crystal roundness and reduced the particle size significantly, despite of the extremely rapid nature of the crystallization process. This method resulted in the α ‐polymorph of glycine with an appropriate low residual additive content and a minimal residual organic solvent content. The arrangement and the optimal concentration of the additive were determined. Abstract : The impinging jet crystallization method was applied for the first time together with different concentrations of potassium chloride as an additive in order to modify the crystal habit of glycine particles. Relevant factors affecting the impinging jet‐crystallized product were identified by a 3 2 full factorial design, revealing the additive concentration and the post‐mixing time as important process parameters.